2017
DOI: 10.3844/ajisp.2017.62.72
|View full text |Cite
|
Sign up to set email alerts
|

Promising Effects of Beta-Glucans on Metabolism and on the Immune Responses: Review Article

Abstract: A public health issue, Diabetes mellitus, affects millions of people around the globe. Ingestion of foods with a low glycemic indexfiber-rich meals-such as beta-glucans, is increasing as an important alternative for diabetes control. These compounds act reducing parameters such as blood glucose, cholesterol and triglycerides, by decreasing the absorption of glucose and lipids by enterocytes and eventually promote weight loss. Beta-glucans are also described as immunomodulatory agents by stimulating phagocytosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 86 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…Among the well-studied pleiotropic effects of β-glucan, we can mention stimulation of both humoral and cellular immunity (Novak and Vetvicka, 2008), metabolic control of diabetes (Wursch and Pi-Sunyer, 1997), stimulation of wound healing (Browder et al, 1988), stress reduction (Vetvicka and Vetvickova, 2014), attenuation of chronic fatigue syndrome (Vetvicka and Vetvickova, 2015), lowering cholesterol levels (Braaten et al, 1994), and inhibition of cancer (Sima et al, 2015). Readers seeking a summary of glucan actions can read a recent monography by Větvička (2013) or other additional excellent reviews (de Oliveira Silva et al, 2017; Vannucci et al, 2017; Bacha et al, 2017; Vetvicka et al, 2017; Alves da Cunha et al, 2017). A schematic view on the role of glucan in stimulation of immune reactions is shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…Among the well-studied pleiotropic effects of β-glucan, we can mention stimulation of both humoral and cellular immunity (Novak and Vetvicka, 2008), metabolic control of diabetes (Wursch and Pi-Sunyer, 1997), stimulation of wound healing (Browder et al, 1988), stress reduction (Vetvicka and Vetvickova, 2014), attenuation of chronic fatigue syndrome (Vetvicka and Vetvickova, 2015), lowering cholesterol levels (Braaten et al, 1994), and inhibition of cancer (Sima et al, 2015). Readers seeking a summary of glucan actions can read a recent monography by Větvička (2013) or other additional excellent reviews (de Oliveira Silva et al, 2017; Vannucci et al, 2017; Bacha et al, 2017; Vetvicka et al, 2017; Alves da Cunha et al, 2017). A schematic view on the role of glucan in stimulation of immune reactions is shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…β-glucans also exert favourable effects on intestinal function and gut health through an activity on intestinal microflora and bacterial metabolites [72]. Additionally, β-glucans from bacterial and fungal origin have recognized benefits for the stimulation of the immune system, as antimicrobial agents and against tumour and metastasis development, and they are used as prevention treatment, as well as in adjuvant therapy [17]. Some evidence also attributes such positive effects to β-glucans from cereal sources.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al described the structure and characteristics of cereal β-glucans in view of their extraction procedures [10]. State-of-the-art studies are available on their potential for glycaemic control in diabetes [16] or for the immune response [17,18]. Analytical methodologies to characterize β-glucans have also been thoroughly examined by some authors [19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the oral administration of Iβ-glucan alleviates the alteration in plasma levels of IFN-γ, TNF-α and Il-6. It was found that Iβ-glucan enhanced the immuno-modulators, which might be may be ascribed to the effect of its constituents that are able to scavenge free radicals (Azab & El-Dawi, 2005;Silva et al, 2015 andSilva et al, 2017). Additionally, Pillai et al (2013) have demonstrated that β-glucan promote the repair of DNA of human lymphocytes and restored the TNF-α generation (Gao et al, 2003).…”
Section: Discussionmentioning
confidence: 99%